Optimalisasi Program Pelatihan untuk Meningkatkan Kinerja dan Kompetensi - Laia, Sari Hati; Rahayu, Enik (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This article aims to analyze the effectiveness of the job training program at LPK Kartika in improving the competency of the workforce to meet the needs of the industry. The focus of this study is the extent to which the training provided can improve the skills of participants and the challenges faced in its implementation. This study refers to the theory of competency-based learning and industry-based job training. Data were collected through observation, semi-structured interviews, and review of documents distributed to training participants, instructors, LPK management, and representatives of related industries. The collected data were analyzed qualitatively using thematic analysis methods to identify the impact of training and the obstacles faced in its implementation. The results of the study indicate that training at LPK Kartika has a positive impact on improving participants' skills, with the majority of participants feeling that the teaching materials and methods are relevant to industry demands. However, the main challenges faced are the limitations of teaching methods, instructor readiness in delivering the material, and the lack of support from the work environment in applying the skills learned. To improve the effectiveness of training, this study recommends a more balanced integration of theory and practice in the curriculum, improving the quality of instructors through further training and development of teaching skills, and utilizing e-learning-based learning platforms to increase flexibility and interactivity in the learning process. With these steps, it is hoped that the training program at LPK Kartika can be more optimal in producing a competitive workforce that is ready to face global competition.